Broadly sympatric occurrence of two thief ant species Solenopsis fugax (Latreille, 1798) and S. juliae (Arakelian, 1991) in the East European Pontic-Caspian region (Hymenoptera, Formicidae) is disclosed - Csősz, Sándor; Seifert, Bernhard; László, Márk; Yusupov, Zalimkhan M.; Herczeg, Gábor (ZooKeys, 2023)
This paper presents numeric morphology-based evidence on the broadly overlapping distribution of two thief ant species Solenopsis fugax (Latreille, 1798) and S. juliae (Arakelian, 1991) in the East European Pontic-Caspian region. The paper integrates two autonomous data collections and independent analyses performed by different researchers, using different equipment, considering different character combinations, and evaluating partially different samples. Five type series, the neotype series of Solenopsis fugax (Latreille 1798) and the type series of S. flavidula (Nylander, 1849), S. (Diplorhoptrum) fugax var. furtiva Santschi, 1934, S. (Diplorhoptrum) fugax var. pontica Santschi, 1934, S. (Diplorhoptrum) fugax var. scytica Santschi, 1934 were nested in one cluster and we propose the junior synonymy of the latter four taxa names with S. fugax . The other cluster contained only one type specimen of Solenopsis nitida (Dlussky & Radchenko, 1994) measured from AntWeb images. The naming of this cluster was based on both verbal statements and measurements of gynes given in the original description of Solenopsis juliae (Arakelian, 1991), which represents the oldest available name for this cluster. Hence, S. nitida is proposed as junior synonym of S. juliae . Solenopsis cypridis Santschi, 1934 is raised to species rank based on investigation of worker and gyne type specimens.